2021
DOI: 10.3390/joitmc7030180
|View full text |Cite
|
Sign up to set email alerts
|

Open Innovation through Customer Satisfaction: A Logit Model to Explain Customer Recommendations in the Hotel Sector

Abstract: Open innovation allows the hotel industry to create platforms and channels for collaboration with its customers, which results in a better understanding of their tastes and demands. In the current environment, which is full of uncertainty, many companies have seen their profits decrease, and even the permanence of their businesses endangered due to the COVID-19 pandemic. In such an environment, it is even more necessary to take into account the customer’s opinion about the service received, since once the cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
17
0
1
Order By: Relevance
“…These resources would enhance the innovative capacity of firms in times of turbulence (Schweitzer et al 2011). Hotels must reinforce innovation to capture precise customer responses, especially during COVID-19 (Díaz and Duque 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These resources would enhance the innovative capacity of firms in times of turbulence (Schweitzer et al 2011). Hotels must reinforce innovation to capture precise customer responses, especially during COVID-19 (Díaz and Duque 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, consumers also hope that companies can collaborate with more partners to be compared when choosing products. The company can realize this expectation by conducting open innovation [21].…”
Section: Discussionmentioning
confidence: 99%
“…Open innovation helps startups to be able to match the needs and desires of consumers [20]. In this sense, the customer becomes a source of open innovation since, through collaboration, they can communicate their needs to the business network [21]. Startups can succeed in implementing open innovation through their websites and technology platforms' security, design, and ease of use [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, we have shown the importance of information sharing-as the core of open innovation [81]-through the PLM processes differently. Studies have shown that constant monitoring and acquiring customers' needs [82] and competitors' offered services [83] is a critical strategy for knowledge transfer in open innovation processes [81] and should be considered as a crucial strategy for accurate sales forecasting and production planning for companies. Also, the share of information between marketing and R&D through the integration of these two parts could help both works with more coordination and meet customers' needs.…”
Section: System Dynamic Model Of Plm and Open Innovationmentioning
confidence: 99%